2018
DOI: 10.3847/1538-4365/aab71e
|View full text |Cite
|
Sign up to set email alerts
|

Abundances and Depletions of Neutron-capture Elements in the Interstellar Medium

Abstract: We present an extensive analysis of the gas-phase abundances and depletion behaviors of neutron-capture elements in the interstellar medium (ISM). Column densities (or upper limits to the column densities) of Ga ii, Ge ii, As ii, Kr i, Cd ii, Sn ii, and Pb ii are determined for a sample of 69 sight lines with high-and/or mediumresolution archival spectra obtained with the Space Telescope Imaging Spectrograph onboard the Hubble Space Telescope. An additional 59 sight lines with column density measurements repor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(79 citation statements)
references
References 99 publications
(216 reference statements)
5
70
4
Order By: Relevance
“…The result for A 3 {Kr, F * } is not as definitive as the determination of A Kr in the study by Ritchey et al (2018), who found that this coefficient differed from zero at the 2.8σ significance level. However, the preferred value of A 3 {Kr, F * } is identical to the value of A Kr listed in J09 and not far from that of Ritchey et al (2018). Our general finding for the strength of the depletions, as indicated by B 3 {Kr}, is less than all previous determinations.…”
Section: Trends That Include Starlight Intensitiescontrasting
confidence: 72%
See 4 more Smart Citations
“…The result for A 3 {Kr, F * } is not as definitive as the determination of A Kr in the study by Ritchey et al (2018), who found that this coefficient differed from zero at the 2.8σ significance level. However, the preferred value of A 3 {Kr, F * } is identical to the value of A Kr listed in J09 and not far from that of Ritchey et al (2018). Our general finding for the strength of the depletions, as indicated by B 3 {Kr}, is less than all previous determinations.…”
Section: Trends That Include Starlight Intensitiescontrasting
confidence: 72%
“…The measurable detections of Kr absorption have a median outcome log(Kr/H tot ) = −8.85. This abundance level is higher than the general levels of around −9.0 reported by earlier investigators (Cardelli & Meyer 1997 ;Cartledge et al 2003Cartledge et al , 2008Ritchey et al 2018), and this disparity probably arises from a recognition in the present study of additional, but not easily apparent, absorptions spanned by the wider velocity intervals defined by the limits of the strongest line of Mg II, as discussed at the beginning of Section 3.1 and highlighted in Figure 2. On average, the earlier investigations may have missed about 30% of the total Kr, which may apply especially for lines of sight HD207308 HD165246 HD75309 HD191877 HD72648 HD147888 HD201345 HD137595 HD208440 HD104705 HD170740 HD115071 HD114886 HD144965 HDE303308 HD94493 HD203374 HD108639 HD99890 HD206267 HD25443 HD101190 HD69106 HD177989 HD209339 HD220057 HD122879 HD152590 HD207198 HD53975 HD219188 HD185418 HD152424 HD151805 HD109399 HD99857 HD152249 HD206773 HD198781 HD40893 HD52266 HD90087 HD91824 HD1383 HD124314 HD103779 HD15137 HD202347 HDE308813 HD97175 HD195455 HD195965 HD93129 HD91983 HD210839 CPD-59 4552 HD92554 HD93843 HD108 HD13268 HD148937 HD198478 HD210809 BD+53 2820 HD192035 HD207538 HDE232522 HD46223 HD99953 CPD-59 2603 HD66788 HD124979 HD93222 HD116781 HD224151 HD218915 HD35914 HD148422 HD41161 HD93205 HD116852 BD+35 4258 HD178487 HD100199 CPD-69 1743 HD168941 HD14818 HD3827 HD63005 HD88115 HD111934 HD13745 HD12323 HD179407 HD167402 HD115455 HD13841 HD89137 HD163522 spanning large distances across other spiral arms in the Galaxy.…”
Section: Significance Of Kr Depletionscontrasting
confidence: 70%
See 3 more Smart Citations